The curious case of auxiliary -manya in Lwitaxo - Robert Botne (Studies in African Linguistics, 2009)
Lwitaxo, one of the Luhya languages of Kenya, has an auxiliary verb of the form -many’a that occurs in compound constructions that express either a generic reading (“normally do V”) or a culminative reading (“ended up V-ing”). This verb is identical in form to the lexical verb -many’a ‘(come to) know’. However, while there are attested cases of KNOW verbs grammaticalizing as habitual/generic auxiliaries, there are no such attestations of KNOW verbs grammaticalizing as indicators of culmination. The author proposes that auxiliary -many’a is the unique result of a convergence of factors—sound change, morphophonological analogy, and semantic reinterpretation—that led an original auxiliary, -mala ‘finish’, to shift in form to resemble lexical -many’a.